76. Intraoperative recording of saphenous nerve somatosensory evoked potentials during spine deformity surgery. Issue 4 (April 2016) - Simioni, V.; Pastorelli, F.; Plasmati, R.; Granieri, E.; Di Silvestre, M.; Tugnoli, V.; Greggi, T.
Abstract : Intraoperative SEPs from lower-extremity are typically elicited by stimulating the posterior tibial nerve. Recently, Silverstein et al. described the novel technique of monitoring saphenous nerve SEP (snSEP) during transpsoas approach to the spine in order to detect femoral nerve injury at the L2–L3–L4 levels. The aim of this study was to record snSEP during spine deformity surgery in order to monitor dorsal column and L2–L3–L4 roots at risk during spinal instrumentation procedures. Twenty consecutive patients were involved. Multimodal-IOM, with MEPs, SEPs (stimulating saphenous and posterior tibial nerves), EMG and pedicle screw stimulation, was employed in the patients. Saphenous nerve was stimulated through needle electrodes placed in between the vastus medialis and sartorius muscles, using a repetition rate of 2.7 Hz and a stimulus intensity of 30–45 mA. The cortical response, recorded at the CPz and Fz location, was a positive downward deflection with reproducible latencies at 30 ms. Saphenous nerve stable SEP was recorded in 18/20 patients. Changes were noted in one patient who presented a bilateral transient reduction of lower limbs MEPs and snSEPs during deformity correction. SnSEP monitoring may be a complementary technique in preserving dorsal columns and upper lumbar roots function during spine surgery.